Adsorptive removal of P(V) and Cr(VI) by calcined Zn-Al-Fe ternary LDHs - Nacera Rezak (IWA Publishing, 2021)
The present study deals with the preparation and structural and adsorbent characterization of the ternary layered double hydroxides (LDHs; ZFA-HT) with molar ratio Zn2+/Al3+/Fe3+ = 2/0.5/0.5 and its product calcined (ZFA-350) at 350 °C, which is examined for the removal of phosphate P(V) and chromate Cr(VI) from aqueous media. The as-obtained materials are characterized by X-ray diffraction (XRD), Fourier-transform infrared (FT-IR), thermogravimetric analysis-differential scanning calorimetry (TGA–DSC), scanning electron microscopy-X-ray energy dispersion (SEM-EDX) and Brunauer–Emmett–Teller (BET). Structural characterizations show that the LDHs is successfully synthesized and its calcined product is a mixed oxide. Batch sorption studies are conducted to investigate the effects of various experimental parameters such as contact time, solution pH, adsorbent amount, initial P(V) or Cr(VI) concentration and temperature. The isotherms, kinetics and thermodynamic parameters of adsorption of phosphate and chromium are studied. The adsorption processes are well described by the pseudo-second-order kinetic model than the other models examined. The adsorption isotherms data fit best to the Langmuir isotherm model instead of Freundlich and Dubinin–Radushkevich models. The maximum monolayer adsorption capacity of ZFA-350 was found to be 140.85 mg/g for P(V) and 52.63 mg/g for Cr(VI). The positive ΔH and ΔS and negative ΔG values reveal that the P(V) and Cr(VI) sorption onto ZFA-350 is endothermic, irreversible and spontaneous in nature. HIGHLIGHTS Synthesis and characterization of [Zn-Al-Fe-CO3] LDHs and its calcined product.; Adsorption of P(V) and Cr(VI) follow the Langmuir isotherm model and pseudo-second-order kinetics.; Thermodynamic analysis exhibits the spontaneous and endothermic nature of the sorption process.; Improvement of the adsorption capacities of P(V) and Cr(VI) compared to other adsorbents used.;